Synchronized Operando Analysis of Graphite Negative Electrode of Li-Ion Battery. Issue 8 (6th August 2021) - Fujimoto, Hiroyuki; Murakami, Miwa; Yamanaka, Toshiro; Shimoda, Keiji; Kiuchi, Hisao; Ogumi, Zempachi; Abe, Takeshi
Abstract : Since the rechargeable Li-ion battery was invented in the early 1990s, its performance has evolved continually and Li-ion batteries are now installed in most mobile devices. In these batteries, graphite is used as a negative electrode material. However, the detailed reaction mechanism between graphite and Li remains unclear. Here we apply synchrotron X-ray diffraction, 7 Li-nuclear magnetic resonance and Raman spectroscopy to operando analysis of the charge/discharge mechanism of a graphite electrode. The spectrum of the graphite electrode is measured repeatedly during the reaction. The operando dataset obtained is then analyzed synchronously with the composition of x in LiC x estimated from the charge/discharge curves. We propose a synchronized operando analysis method that provides useful information about the behavior of the C–C bond vibration mode and the interactions between Li and carbon atoms due to structural change during the charge/discharge reaction. In addition, we determine details of the intercalation mechanism.